A methodology for on‐board CBCT imaging dose using optically stimulated luminescence detectors. (8th September 2016) - Mail, Noor; Yusuf, Muhammad; Alothmany, Nazeeh; Kinsara, A. Abdulrahman; Abdulkhaliq, Fahad; Ghamdi, Suliman M.; Saoudi, Abdelhamid
Abstract : Cone‐beam computed tomography CBCT systems are used in radiation therapy for patient alignment and positioning. The CBCT imaging procedure for patient setup adds substantial radiation dose to patient's normal tissue. This study presents a complete procedure for the CBCT dosimetry using the InLight optically‐stimulated‐luminescence (OSL) nanoDots. We report five dose parameters: the mean slice dose ( D MSD ); the cone beam dose index ( CBDI W ); the mean volume dose ( D MVD ); point‐dose profile, D(FOV); and the off‐field Dose. In addition, CBCT skin doses for seven pelvic tumor patients are reported. CBCT‐dose measurement was performed on a custom‐made cylindrical acrylic body phantom (50 cm length, 32 cm diameter). We machined 25 circular disks (2 cm thick) with grooves and holes to hold OSL‐nanoDots. OSLs that showed similar sensitivities were selected and calibrated against a Farmer‐type ionization‐chamber (0.6 CT) before being inserted into the grooves and holes. For the phantom scan, a standard CBCT‐imaging protocol (pelvic sites: 125 kVp, 80 mA and 25 ms) was used. Five dose parameters were quantified: D MSD, CBDI W, D MVD, D(FOV), and the off‐field dose. The D MSD for the central slice was 31.1 ± 0.85 mGy, and CBDI W was 34.5 ± 0.6 mGy at 16 cm FOV. The D MVD was 25.6 ± 1.1 mGy. The off‐field dose was 10.5 mGy. For patients, the anterior and lateral skin doses attributable to CBCT imaging were 39.04 ± 4.4 and 27.1 ± 1.3 mGy, respectively. OSL nanoDots were convenient to use in measuring CBCT dose. The method of selecting the nanoDots greatly reduced uncertainty in the OSL measurements. Our detailed calibration procedure and CBCT dose measurements and calculations could prove useful in developing OSL routines for CBCT quality assessment, which in turn gives them the property of high spatial resolution, meaning that they have the potential for measurement of dose in regions of severe dose‐gradients. PACS number(s): 87.57.‐s, 87.57.Q, 87.57.uq